Sisi Yang Terlupa: Peran Historis Ahmadiyah Dalam Wacana Gerakan Modernisasi Islam Di Indonesia - Ropi, Ismatu (AL-ADYAN, 2020)
If compared with other Indonesian Islamic organizations, histroy of Ahmadiyah is a topic that had been little discussed. Ahmadiyah is like a forgotten dot in the the prolonged history of Indonesia.  Ahmadiyah has been in the archiplego for more than eighty years agos, but its existence is even until today still under suspicious eyes for many reasons, either theological particularly due to the acceptance of new prophethood; or its social attitude for being exclusive and due to political conpirative reason alleging Ahmadiyah as being aimed at weakening Islam from within. Apart from those controversies, not many people aware that Ahmadiyah, either the Qadianis or Lohoreans, have once contributed to the history of Islamic modernization in Indonesia. This article tries to depct in general how Ahmadiyah has been paving the way that contribute to the shaping if modern Islamic discource and movement in Indonesia.